Implementation of TGT Type Cooperative Learning on Colloidal Materials to Improve Student Learning Outcomes and Activeness - Endiyana Pratiwi (LPPM Universitas Negeri Jakarta, 2024)
Education today requires teachers to be able to meet targets, both quality and quantity of educational goals. The use of learning methods that are interesting, fun, active, and challenged, the learning delivered will be meaningful. Cooperation and responsibility will be realized, the quality of learning will improve, and learning outcomes will be high. This research was conducted with the aim of: (1) making learning tools using TGT type cooperative learning (2) knowing the effect of colloid material learning tools using TGT type cooperative learning on student activeness and learning outcomes. The research was conducted in two stages, namely: (1) The stage of making learning devices, including: syllabus, Learning Implementation Plan (RPP), colloid material for online class presentation, games, worksheets for percentage, power point for class presentation, independent practicum sheet, learning outcomes evaluation, student activity observation sheet, teacher performance observation sheet, (2) The implementation stage of learning devices. The results of the study (1) the teacher together with the team made learning devices through a series of processes and continued to collect research data. (2) the results of improving learning outcomes Cycle I 77.17, Cycle II 83.23, average 79.09 classified as good. For student activity Cycle I 3.09, Cycle II 3.38 average 3.24 good category, teacher performance Cycle I 3.40 Cycle II 3.55, average 3.48 very good category, the student center learning model will be conducive to building competence, so that problems can be resolved.